Resíduos de fentoato em tomate - Raetano, Carlos Gilberto [UNESP]; Debatista, G. C. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1995)
The objective of the present research was to study the degradation and the persistence of phenthoate (Elsan 50 CE) residues in tomato fruits. The experiment was set in a tomato field located in Mombuca, State of São Paulo, Brazil, after 45 days from seedlings transplantation. Dosages of 600 (A), 800 (B), 1200 (C) and 1600 g a.i./ha (D) were sprayed at the beginning of the ripening period of fruits. Samples of 15 fruits each were collected 1, 4, 10, 20 and 40 days after products spraying. The utilized procedure consisted of extraction with acetone and purification by partition with dichloromethane. The purified extract was concentrated and injected into a gas chromatograph equipped with alkaly flame ionization detector (AFID). The limits of detection were of 0,01 ppm for this product. The recovery percentage from fortified samples varied from 60 to 81%. The degradation and the persistence half-lives were 1 to 2 and 3 to 6 days for phenthoate, respectively.

No presente trabalho, procurou-se estudar a degradação e persistência dos resíduos de fentoato (Elsan 50 CE) em frutos de tomate. O experimento foi instalado no município de Mombuca, SP, em área de cultivo de tomate estaqueado, 45 dias após o transplantio das mudas. O produto foi aplicado com o auxílio de um pulverizador costal manual, no início do período de maturação dos frutos, nas dosagens de 600 (A), 800 (B), 1200 (C) e 1600 g de i.a./ha (D). Os frutos foram amostrados com 1, 4, 10, 20 e 40 dias após a aplicação. O método de análise utilizado constou de extração com acetona e purificação por partição em diclorometano. O extrato foi concentrado e injetado em cromatógrafo a gás, equipado com detector de ionização de chama alcalina (DICA). Esse método proporcionou um limite de detecção de 0,01 ppm para esse produto. As porcentagens de recuperação em amostras fortificadas, em diferentes concentrações, variaram de 60 a 81%. Os valores de meia-vida de degradação e de persistência para fentoato foram de 1-2 e 3-6 dias, respectivamente, para as dosagens estudadas.
Residue determination of phenthoate in tomato fruits
Keywords: GAS CHROMATOGRAPHY; INSECTICIDE RESIDUE; LYCOPERSICON ESCULENTUM